A novel combination of methods identifies priority conservation areas for an endemic California Current seabird. Issue 9 (5th July 2022) - Soldatini, Cecilia; Albores‐Barajas, Yuri V.; Rosas‐Hernandez, Martha P.; Handley, Jonathan; Beal, Martin; Dias, Maria P.; Dell'omo, Giacomo
Abstract: There are growing pressures on marine biodiversity. Seabirds in particular are one the most‐threatened groups. The black‐vented shearwater ( Puffinus opisthomelas ) is endemic to Mexican islands and the only shearwater living its entire life cycle in the California Current System, one of the most productive large marine ecosystems in the world. Marine Protected Areas (MPAs) in this region, however, were designed without consideration of accurate data on seabird distributions. Here, 57 black‐vented shearwaters were GPS‐tracked from their main breeding colony (95% of the global population) over four seasons (2016–2019) to estimate their at‐sea distribution. Two methods were applied to identify priority conservation areas: the approach developed by BirdLife International to identify marine Important Bird and Biodiversity Areas and a method using expectation‐maximization binary clustering to identify core foraging areas. One potential marine Important Bird and Biodiversity Area close to the breeding colony and five core foraging areas were identified. These priority conservation areas were largely beyond the bounds of the current MPA network in the region. Our results detail opportunities for improving the implementation of conservation and management measures in the California Current System region with respect to seabirds. The approach of combining site identification methods can be applied to other seabird species for which high‐resolution tracking data are available and can help guide conservation action plans and MPA design.